Analyze the Rate of Late Arrival in Patients with Acute Myocardial Infarction and the Factors That Cause it - Naveed Yaqoob, Iqtidar Ud Din, Muhammad Shahid, Yasir Mansoor, Mujeebullah Tareen, Fahad Khalid, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Explore the causes of patients' delayed hospital visits after presenting with acute myocardial infarction to better understand this issue. Study Design: Cross-sectional Place & Duration: Department of Cardiology, Rawal Institute of Health Sciences, Islamabad during the period from February, 2022 to July, 2022. Methods: Seventy patients of both sexes were enrolled in this study, all of whom had been diagnosed with acute myocardial infarction. Ages of patients ranged from 18 to. A patient's age, sex, place of residence, level of education, and socioeconomic position were meticulously noted. It was recorded how often people were running late. Reasons for the late arrival were calculated. Results: There were a total of 70 patients, 48 (70%) of whom were male and 22 (30%) female. Patients between the ages of 41 and 50 made up the largest age group, followed by those between the ages of 51 and 65. It was found that 42 patients (62.9%) arrived more than 2 hours after their symptoms had begun. The use of public transportation was the leading cause of arrival delays (51.4%), followed by large distance (more than 20 km) (38.5%) and the lack of an attendant (38.5%). Conclusion: We found that a significant proportion of patients with acute myocardial infarction had a delayed arrival. The most common causes of late arrival at the hospital were the use of public transportation, travel distance, lack of education, and low socioeconomic level. Keywords: Delayed arrival, Risk factors, Acute myocardial infarction,